Asymmetric Intermolecular Rauhut−Currier Reaction for the Construction of 3, 3‐Disubstituted Oxindoles with Quaternary Stereogenic Centers. Issue 22 (27th September 2017) - Wang, Hongyu; Wang, Kaiye; Man, Yunquan; Gao, Xiaonan; Yang, Limin; Ren, Yanfei; Li, Na; Tang, Bo; Zhao, Gang
Abstract: A remote cross Rauhut−Currier reaction utilizing vinyl ketones and para ‐quinone methides derived from isatins was realized, which was successfully catalyzed using bifunctional phosphines, furnishing chiral 3, 3‐disubstituted oxindoles in excellent enantioselectivities and high yields. The mechanistic studies demonstrated the key role of the alkyl hydrogen of the vinyl ketones, which conceivably interacted with the para ‐quinone methide carbonyl group via the hydrogen bond, offering a new insight for the design of novel asymmetric reactions. Abstract :